Effect of Fiscal Decentralization on the Attraction of FDI in Iran - mohammad alizadeh; Seyed Ehsan Hosseinidoust; Abolghasem Golkhandan (فصلنامه پژوهش‌های اقتصادی ایران, 2019)
From a financial perspective, decentralization is a transfer of resources from the central government to local governments. Fiscal decentralization policies can lead to more FDI attraction by increasing the share of provincial government funding to local infrastructure.Accordingly, the major purpose of this study is to evaluate the long run and short run impact of fiscal decentralization on FDI in Iran during the period 1992-2014. For this purpose the three indicators of fiscal decentralization of revenue, fiscal decentralization of expenditures, fiscal decentralization of autonomy power and also some control variables including inflation, exchange rate fluctuations, and degree of trade openness have been used.In order to estimate the model, the Johansen-Juselius method and Vector Error Correction Model (VECM) have been applied. Based on the results of the model, all three fiscal decentralization indicators increase FDI in the long run and in the short run. Therefore, providing the necessary conditions for the expansion of fiscal decentralization can help to promote the FDI level in Iran.Also, both in the long run and the short run, inflation and exchange rate fluctuations have a negative effect, and the degree of trade openness has a positive effect on FDI.